Standardized Kaempferia parviflora Wall. ex Baker (Zingiberaceae) Extract Inhibits Fat Accumulation and Muscle Atrophy in ob/ob Mice. (28th May 2018) - Lee, Sunkyu; Kim, Changhee; Kwon, Dowan; Kim, Mi-Bo; Hwang, Jae-Kwan
Abstract : Obesity, a metabolic disorder caused by an imbalance between energy intake and energy expenditure, is accompanied with fat accumulation and skeletal muscle atrophy. Kaempferia parviflora Wall. ex Baker, also called black ginger, is known to increase physical fitness performance and improve energy metabolism. In this study, we investigated whether Kaempferia parviflora extract (KPE) alleviates both obesity and muscle atrophy using ob/ob mice. Wild-type C57BL/6J and ob/ob mice were provided with a normal diet ad libitum, and ob/ob mice were orally given KPE at a dose of 100 mg/kg/day or 200 mg/kg/day for eight weeks. KPE significantly decreased body weight, fat volume, and fat weight without affecting appetite. It inhibited the expression of adipogenic transcription factors and lipogenic enzymes by upregulating AMP-activated protein kinase (AMPK) in epididymal fat. In contrast, it markedly increased the muscle fiber size, muscle volume, and muscle mass, resulting in the enhancement of muscle function, such as exercise endurance and grip strength. On the molecular level, it activated the phosphatidylinositol 3 kinase (PI3K)/Akt pathway, a key regulator in protein synthesis in skeletal muscle. KPE could be a promising material to alleviate obesity by inhibiting adipogenesis, lipogenesis, and muscle atrophy.